Choroidal Vascularity Index as a Biomarker for Visual Response to Antivascular Endothelial Growth Factor Treatment in Diabetic Macular Edema. (26th November 2021) - Dou, Ningxin; Yu, Shanshan; Tsui, Ching-Kit; Yang, Boyu; Lin, Jianqiang; Lu, Xi; Xu, Yue; Wu, Benjuan; Zhao, Jinfeng; Liang, Xiaoling
Abstract : Purpose . To investigate the choroidal vascularity index (CVI) as a prognostic factor for the visual efficacy of antivascular endothelial growth factor (VEGF) treatment in diabetic macular edema (DME). Methods . We retrospectively reviewed 92 DME eyes receiving anti-VEGF treatment, which were stratified as responders (≥5 letters gained) and nonresponders (<5 letters gained or lost). Baseline systematic features and optical coherence tomography features, including the CVI, adjusted ellipsoid zone (EZ) reflectivity, subretinal fluid (SRF), and disorganization of the retinal inner layers (DRIL), were evaluated between the two groups. Results . The baseline CVI was significantly lower in nonresponders than in responders (0.66 ± 0.05, 0.69 ± 0.05, and 0.72 ± 0.05, p = 0.014 ). After adjusting for other factors, the baseline CVI, DRIL, SRF, and adjusted EZ reflectivity were significantly associated with visual outcomes (CVI: odds   ratio   OR = 0.17, p = 0.006 ; adjusted EZ reflectivity: OR = 0.56, p = 0.007 ; DRIL: OR = 6.71, p = 0.001 ; and SRF: OR = 0.29, p = 0.008 ). Conclusion . DME patients with a higher CVI, higher adjusted EZ reflectivity, the presence of SRF, and the absence of DRIL at baseline were more likely to gain >5 letters in visual acuity after anti-VEGF treatment. CVI may serve as a novel biomarker for visual response to anti-VEGF treatment in DME.